Photonic crystal fiber mapping using Brillouin echoes distributed sensing - Stiller, Birgit; Foaleng, S. M.; Beugnot, J. -C.; Lee, M. W.; Delque, M.; Bouwmans, Geraud; Kudlinski, Alexandre; Thevenaz, Luc; Maillotte, H.; Sylvestre, Thibaut (Optics Express, 2010)
In this paper we investigate the effect of microstructure irregularities and applied strain on backward Brillouin scattering by comparing two photonic crystal fibers drawn with different parameters in order to minimize diameter and microstructure fluctuations. We fully characterize their Brillouin properties including the gain spectrum and the critical power. Using Brillouin echoes distributed sensing with a high spatial resolution of 30 cm we are able to map the Brillouin frequency shift along the fiber and get an accurate estimation of the microstructure longitudinal fluctuations. Our results reveal a clear-cut difference of longitudinal homogeneity between the two fibers. © 2010 Optical Society of America.
CRIS-Team Scopus Importer:2021-06-29